The Role of the Third Mission in Sustainable Development: Reflections on the Experiences of Two American Universities - Alalwany, حميد; Waheeb, سهل (Journal of King Abdulaziz University: Environmental Design Sciences, 2021)
Universities are intended to play an important and major role in sustainable development. To fulfill this role, they must take the lead in the development processes of knowledge economy and society, particularly in two main areas: the first is innovation and entrepreneurship, and the second is the production, incubation and transfer of knowledge and technology, or the so-called third mission of universities. The aim of this paper is to address the role of the third mission in promoting sustainable development, and the ways in which universities can develop their main functions. This includes fulfilling their duties (1) in education and training, (2) in research and development, (3) in production, incubation and transfer of knowledge and technology, (4) in supporting innovation and entrepreneurship, and (5) in building intellectual capital. In order to achieve the aim of the paper, the following objectives were identified: 1. Addressing the perceptions of the third mission as a concept, 2. Analyzing the main functions of universities in the era of knowledge economy and integration between these functions, 3. Addressing the concept of an entrepreneurial university, and 4. Analyzing and evaluating the experiences of two American universities in developing the knowledge economy and knowledge society, and their efforts in supporting sustainable development. The research results revels that Stanford University is an outstanding example of the third mission with a strong academic and leadership position that has enabled it to become the world's first leading university. The second outstanding model is the Massachusetts Institute of Technology, which is renowned as a first-class research institute with a focus on physical science, technology and engineering. Universities have become increasingly involved in the task of transferring and localizing knowledge and techniques over recent decades. This role is played by universities through the establishment of institutes and centers for the transfer and resettlement of knowledge and technology, technology licensing centers, business incubators, knowledge and technology parks, and venture capital funds for start-ups.